Association of BAFF and IL‐17A with subphenotypes of primary Sjögren's syndrome. (4th May 2015) - Deng, Fengyuan; Chen, Juan; Zheng, Junfeng; Chen, Yan; Huang, Renliang; Yin, Junping; Gao, Xing; Lin, Qingyan; Huang, Chaoyang; Gao, Yushan; Yu, Xinhua; Liu, Zuguo
Abstract: Aim: Primary Sjögren's syndrome (pSS) is an autoimmune disease affecting exocrine glands. Both autoreactive T cells and B cells are involved in the development of pSS, but their exact contribution to the pathogenesis is not clear. Here, we aimed to investigate the association of B‐cell activating factor (BAFF) and interleukin (IL)‐17A with subphenotypes of pSS. Methods: Peripheral blood samples were collected from 31 pSS patients and 28 healthy controls. The serum levels of BAFF and IL‐17A were quantified by sandwich ELISA. Results: The increased circulating BAFF levels are associated with higher immunoglobulin G (IgG) levels ( P  =   0.0167) and anti‐Ro/SS antigen A autoantibody ( P  =   0.032), while the elevated circulating levels of IL‐17A are associated with lower C3 levels ( P  =   0.0213) and higher focus score of salivary gland tissue ( P  =   0.002). Conclusion: Our results show that BAFF and IL‐17A are associated with different subphenotypes of pSS, suggesting both humoral and cellular immune response are involved in the pathogenesis of pSS.